Efficacy of bifidobacterium animalis subsp. lactis (BB-12), b. infantis and lactobacillus acidophilus (La-5) probiotics to prevent gut dysbiosis in preterm infants of 28+0-32+6 weeks of gestation: a randomised, placebo-controlled, double-blind, multicentre trial : the PRIMAL clinical study protocol - Marißen, Janina; Haiß, Annette; Meyer, Claudius; Rossum, Thea Van; Bünte, Lisa Marie; Frommhold, David; Gille, Christian; Goedicke-Fritz, Sybelle; Göpel, Wolfgang; Hudalla, Hannes; Pagel, Julia; Pirr, Sabine; et al. (BMJ open, 2019)
Introduction The healthy ‘eubiosis’ microbiome in infancy is regarded as the microbiome derived from term, vaginally delivered, antibiotic free, breastfed infants at 4-6 months. Dysbiosis is regarded as a deviation from a healthy state with reduced microbial diversity and deficient capacity to control drug-resistant organisms. Preterm infants are highly sensitive to early gut dysbiosis. Latter has been associated with sepsis and necrotising enterocolitis, but may also contribute to long-term health problems. Probiotics hold promise to reduce the risk for adverse short-term outcomes but the evidence from clinical trials remains inconclusive and none has directly assessed the effects of probiotics on the microbiome at high resolution. - Methods and analysis A randomised, double blind, placebo-controlled study has been designed to assess the safety and efficacy of the probiotic mix of Bifidobacterium animalis subsp. lactis, B. infantis and Lactobacillus acidophilus in the prevention of gut dysbiosis in preterm infants between 28+0 and 32+6 weeks of gestation. The study is conducted in 18 German neonatal intensive care units. Between April 2018 and March 2020, 654 preterm infants of 28+0-32+6 weeks of gestation will be randomised in the first 48 hours of life to 28 days of once daily treatment with either probiotics or placebo. The efficacy endpoint is the prevention of gut dysbiosis at day 30 of life. A compound definition of gut dysbosis is used: (1) colonisation with multidrug-resistant organisms or gram-negative bacteria with high epidemic potential or (2) a significant deviation of the gut microbiota composition as compared with healthy term infants. Dysbiosis is determined by (1) conventional microbiological culture and (2) phylogenetic microbiome analysis by high-throughput 16S rRNA and metagenome sequencing. Persistence of dysbiosis will be assessed at 12-month follow-up visits. Side effects and adverse events related to the intervention will be recorded. Key secondary endpoint(s) are putative consequences of dysbiosis. A subgroup of infants will be thoroughly phenotyped for immune parameters using chipcytometry. - Ethics and dissemination Ethics approval was obtained in all participating sites. Results of the trial will be published in peer-review journals, at scientific meetings, on the website (www.primal-study.de) and via social media of parent organisations. - Trial registration number DRKS00013197; Pre-results.
Gesehen am 14.10.2020